A Review on Marathi Braille - Madhav A. Kankhar; Dr. C Namrata Mahender (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper investigates the complex process of translating Marathi text into Bharati Braille, emphasizing the critical importance of equitable information access for individuals with visual impairments. It provides an in-depth analysis of Bharati Braille’s structure, encoding guidelines, and its adaptation to Indian languages, with a particular focus on Marathi’s linguistic features and challenges. Through a comprehensive literature review, the study examines existing text-to-Braille conversion technologies, analyzing hardware and software solutions and their applicability to Marathi. Key challenges such as linguistic nuances, dialectical variations, and the preservation of semantic integrity during translation are explored in detail. The paper highlights technical barriers, including encoding complexities and readability issues, and stresses the need for innovative solutions to address these gaps. By offering actionable insights, this research supports the development of advanced text-to-Braille systems tailored to Marathi, fostering inclusivity and enhancing access to education and information for visually impaired individuals. This study aims to contribute to the broader goal of promoting social and educational inclusion, empowering individuals with visual impairments to participate fully in society.